Effect Of Product Quality, Promotion, Price And Service On Consumer Decisions At Suzuya Mall Rantauprapat Shopping Center - Ramadani, Sri; Nasution, Novrihan Leily; Arjuna, Syukron (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to examine the effect of product quality, promotion, price, and service quality on consumer purchasing decisions at Suzuya Mall Rantauprapat. Methodology: This research uses a quantitative approach by collecting primary data through questionnaires distributed to consumers of Suzuya Mall Rantauprapat using a Likert scale. The data were analyzed using multiple linear regression supported by validity, reliability, and classical assumption tests. Results: The results show that product quality, promotion, price, and service quality each have a positive and significant effect on consumer purchasing decisions. Simultaneously, all independent variables significantly influence purchasing decisions. Novelty: This study presents an integrated analysis of product, promotion, price, and service quality factors in influencing purchasing decisions within a regional retail mall context. Findings: Promotion is identified as the most dominant factor affecting consumer purchasing decisions, followed by product quality, service quality, and price. Originality: The originality of this study lies in its empirical evidence derived from a local retail setting, providing insights into consumer behavior in regional shopping centers. Conclusions: Enhancing product quality, promotional strategies, pricing policies, and service performance can effectively increase consumer purchasing decisions. Type of Paper: Empirical Research Paper.